Bottom, Top, or in Between: Combining Plasmonic Nanohole Arrays and Hydrogel Microgels for Optical Fiber Sensor Applications. Issue 15 (11th April 2022) - Polley, Nabarun; Werner, Peter; Balderas‐Valadez, Ruth F.; Pacholski, Claudia
Abstract: Attractive label‐free plasmonic optical fiber sensors can be developed by cleverly choosing the arrangement of plasmonic nanostructures and other building blocks. Here, the final response depends very much on the alignment and position (stacking) of the individual elements. In this work, three different types of fiber optic sensing geometries fabricated by simple layer‐by‐layer stacking are presented, consisting of stimulus‐sensitive poly‐ N ‐isopropylacrylamide (polyNIPAM) microgel arrays and plasmonic nanohole arrays (NHAs), namely NHA/polyNIPAM, polyNIPAM/NHA, polyNIPAM/NHA/polyNIPAM. Their optical response to a representative stimulus, namely temperature, is investigated. NHA/polyNIPAM monitors the volume phase transition of polyNIPAM microgels through changes in the spectral position and the amplitude of the reflection minimum of plasmonic NHA. In contrast, polyNIPAM/NHA shows a more complex response to the swelling and collapse of polyNIPAM microgels in their reflectance spectra. The most pronounced changes in optical response are observed by monitoring the amplitude of the reflectance minimum of this sensor during heating/cooling cycles. Finally, the triple stack of polyNIPAM/NHA/polyNIPAM at the end of a optical fiber tip combines the advantages of the NHA/polyNIPAM, polyNIPAM/NHA double stacks for optical sensing. The unique layer‐by‐layer stacking of microgel and nanostructure is customizable and can be easily adopted for other applications. Abstract : Various sensors are fabricated by stacking layers of hydrogel microgels and plasmonic nanohole arrays on tips of optical fibers. Their optical response to stimuli shows remarkable differences in the spectral position and intensity of the plasmonic reflectance minimum, which depend on the composition of the stack. The efficient fabrication strategy paves the way to mass production of tailor‐made sensors.